Marketing Management of Islamic Financial Services in the Digital Era - Hayati, Leni Riski; Habibi, Ahmad; Fasa, Muhammad Iqbal (Best Journal of Administration and Management, 2025)
The research aims to analyze in depth the marketing management of Islamic financial services in the digital era, which is currently at a historical crossroads due to the acceleration of digital transformation and the Industrial Revolution 4.0. This study uses a qualitative approach with the method of Systematic Literature Review (SLR). The results of the analysis indicate that adaptation to the Sharia digital marketing mix (7PS), such as technology-based products and physical evidence that transform into digital evidence, must be integrated with strict Sharia compliance. Managerial success depends on Shariah-compliant innovation, strengthening cybersecurity, and Human Resource Investment with dual competencies, with the Sharia Banking-as-a-Service model proposed as a solution to address inequalities in the digital infrastructure of SMEs.